Tahlil Hajat al-Darisin fi KPTM fi Ta'allum al-Lughah al-Arabiyyah li Aghrad Siyahiyyah 'Abra Syabakah Internet - Abd Ghani, Muhammad Taufik; Wan Daud, Wan Ab Aziz; Mohd Mokhtar, Nur Najihah; Sahrir, Muhammad Sabri (Penerbit UPSI, Perak Darul Ridzuan., 2021)
A book chapter published by UPSI Press 2021.